PENGARUH LITERASI KEUANGAN DAN PENDAPATAN TERHADAP PERILAKU KEUANGAN PELAKU UMKM DI DESA GEMPOL - ILFI NURRAHMA; Achmad Wicaksono (Jurnal Riset Akuntansi, 2025)
This study aims to determine the effect of Financial Literacy and Income on the Financial Behavior of MSMEs in Gempol Village using quantitative methods. The independent variables in this study are Financial Literacy and Income, while the dependent variable is Financial Behavior. The sample of this study was 50 MSME respondents selected through random sampling. The result of the t-test showed that Financial Literacy t-count 4,408 > t-table 2,012 and a significant value of 0,000 < 0,05 and Income t-count 2,314 > t-table 2,012 and a significant value of 0,025 < 0,05 had a significant effect on Financial Behavior. The F test also showed a significant simultaneous effect of 0,000 < 0,05, so that both independent variables together influenced the Financial Behavior of MSMEs. Therefore, increasing Financial Literacy is important so that MSMEs can make the right decisions and improve their business performance.